Mechanistic determination using arrays of variable-sized channel microband electrodes: The oxidation of ascorbic acid in aqueous solution - Prieto, F; Coles, B; Compton, R (1998)
"Two-dimensional voltammetry" using arrays of variable-sized gold channel microband electrodes in combination with variable flow rate measurements together with independent gold rotating disk electrode (RDE) data is applied to characterize the oxidation mechanism of L-ascorbic acid (AH2) to dehydro-L-ascorbic acid in aqueous solutions. At pH 2.1 and very low mass transport conditions the reaction is consistent with a CECE mechanism, while at higher mass transport conditions an ECfastCE mechanism is followed. At pH 6.7, the results are again consistent with an ECE mechanism. The following mechanism is proposed: AH2 ⇌ AH- + H+ (kCEE), AH- → AH• + e, AH• → A• - + H+ (kECE). A• - → A + e (CECE); AH2 ⇌ AH2+ + e, AH2+ → AH• + H+(fast), AH• → A• - + H+ (kECE), A•- → A + e (ECfastCE); where, only the first pathway applies at pH 6.7, AH- being the starting species. Values of 3.4 × 103 s-1 and 500 s-1 are found for the rate constants kCEE and kECE, respectively.